THE AESTHETIC DIMENSION OF SPACE IN CONTEMPORARY CERAMICS - Abdulkareem Daabool Obaid; Dr. Mohsen Reda Alkizwini (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The purpose of this paper is to identifying the concept of aesthetic dimensions in contemporary ceramics. As well as Identifying the aesthetic space and its concept in contemporary ceramics, and Confirmation of the effect of aesthetic space by reading a number of paintings of an aesthetic nature and contrasting space. Art in general, and painting in particular, was and still represents a sophisticated type of social awareness capable of depicting the dialectic of the conflict between man and himself and between him and the surrounding world. For this reason, it was agreed that art has the property of documenting its victories and defeats, as well as its beliefs through the forms proposed in this period of a time or that. The human arts in general and the plastic arts in particular are related to references and contexts of knowledge that discover their local identity in relation to the civilization that arose under it and are considered its roots, and it is quite clear that the most important cultural elements that helped the growth and development of peoples is the creation of writing that has great importance in guiding aspects of life different. Through the different eras of the development of the art of ceramics, which formed a basic material in the production of works, but it formed infinite connotations in the use of crafts, and pointed to the possibility of the potter to manipulate the shape of the crafts through its shape and form, and the employment of the colors that he uses through his ceramic work. The fine movement in Iraq benefits students. And art connoisseurs. The Fine and Aesthetic Library sings in art institutions in Iraq.